Upper airway stimulation therapy and sleep architecture in patients with obstructive sleep apnea. (7th May 2019) - Bohorquez, Dominique; Mahmoud, Ahmad F.; Yu, Jason L.; Thaler, Erica R.
Abstract : Objectives/Hypothesis: To quantify changes in sleep architecture before and after upper airway stimulation (UAS) therapy in patients with obstructive sleep apnea. Study Design: Retrospective chart review. Methods: This study was performed at a single‐institution tertiary academic care center. Patients who responded successfully to UAS implantation were selected for this study. Preoperative and postoperative sleep studies were compared to determine sleep architecture changes. Primary outcomes included sleep architecture parameters such as N1, N2, N3, and rapid eye movement (REM) in addition to others. Secondary outcomes included body mass index. Results: Thirty‐five patients met inclusion criteria for this study. There was significant improvement across several sleep architecture parameters. N1 sleep percent decreased from 16.7% ± 2.1% preoperatively to 10.1% ± 1.6% postoperatively ( P = .023). Time spent in N2 increased from 148.0 ± 12.4 minutes to 185.5 ± 10.4 minutes ( P = .030), whereas N3 increased from 21.9 ± 5.0 minutes to 57.0 ± 11.1 minutes ( P = .013). No significant changes were observed in REM sleep. Arousal index decreased from 38.8 ± 4.0 to 30.3 ± 4.0 ( P = .050). Conclusions: There was significant improvement across several sleep architecture parameters among patients who responded successfully to UAS implantation. Level of Evidence: 4 Laryngoscope, 130:1085–1089, 2020